Unilateral Fusion of Maxillary Lateral Incisor: Diagnosis Using Cone Beam Computed Tomography - Iury Oliveira Castro; Carlos Estrela; Vinícius Rezende Souza; Lawrence Gonzaga Lopes; João Batista de Souza (Case Reports in Dentistry)
Objective. The objective of this paper is to report a dental fusion case focusing on clinical and radiographic features for the diagnosis. Method. To report a case of right maxillary lateral incisor fusion and a supernumerary tooth, the anatomy of the root canal and dental united portion were assessed by cone beam computed tomography (CBCT). Results. The clinical examination showed dental juxtaposition with the absence of interdental papilla and esthetic impairment in the right maxillary lateral incisor region. The periapical radiography did not provide enough information for the differential diagnosis due to the inherent limitations of this technique. CBCT confirmed the presence of tooth fusion. Conclusion. CBCT examination supports the diagnosis and provides both the identification of changes in tooth development and the visualization of their extent and limits.